A DISCOURSE HISTORICAL ANALYSIS ON LOCAL CULTURE IN THE FIRST BOOK TRILOGY “RONGGENG DUKUH PARUK” OF AHMAD TOHARI - Sri Sugiharti (Universitas Riau Kepulauan, 2018)
Local culture is commonly used to characterize the experience of everyday life in specific, identifiable localities. It reflects ordinary people's feelings of appropriateness, comfort, and correctness—attributes that define personal preferences and changing tastes. The socio-cultural of Javanese especially in Jatilawang Banyumas. Through the trilogy of “Ronggeng Dukuh Paruk”. Through its discursive strategies, the text presents that the cultural life of Javanese people at that time is mostly influenced by Hinduism. In economic side, Javanese people generally work in farming field. Meanwhile, the cultural condition indicates the pluralistic life of Javanese community. The present research’s effort is to examine the representation of Javanese local culture in an old text entitled “Ronggeng Dukuh Paruk”. Framed generally by CDA (Critical Discourse Analysis) theory and method, and particularly DHA (Discourse Historical Approach), the examination is focused on observing the five discursive strategies in micro- analysis under DHA, which includes strategies of nomination, predication, argumentation, perspectivation, and mitigation. The discussion also highlights the socio-cultural background of Javanese people in that period to see its influence on the content of the text itself. Thus, the integration of two disciplinaries of historical study and linguistics is well-achieved.Keyword: historical discourse analysis, local culture, first book triogy “Ronggeng Dukuh Paruk”.